The Canterbury Tales - Chaucer, Geoffrey (Penguin Classics, 2003)
The procession that crosses Chaucer's pages is as full of life and as richly textured as a medieval tapestry. The Knight, the Miller, the Friar, the Squire, the Prioress, the Wife of Bath, and others who make up the cast of characters -- including Chaucer himself -- are real people, with human emotions and weaknesses. When it is remembered that Chaucer wrote in English at a time when Latin was the standard literary language across western Europe, the magnitude of his achievement is even more remarkable. But Chaucer's genius needs no historical introduction; it bursts forth from every page of The Canterbury Tales.